2014
DOI: 10.1007/s10157-014-1068-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hematuria on the outcome of IgA nephropathy with mild proteinuria

Abstract: Severe hematuria at the time of biopsy naturally improved without any intensive therapy, and there were no negative effects of hematuria on the outcome of IgAN with mild proteinuria. Its prognosis was relatively good, and the treatment of RAS inhibitors might prevent from progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…Although some studies suggested a significant influence of hematuria on the risk of developing ESRD, 6,9,19,20 others could not confirm this finding. [21][22][23][24] However, the robustness of these studies was reduced by the way in which hematuria was evaluated (at the onset of the disease, at the time of renal biopsy, or by cross-sectional studies) without longitudinal data. 23,24 In other studies, urine dipsticks were used, and the magnitude of hematuria was not quantified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies suggested a significant influence of hematuria on the risk of developing ESRD, 6,9,19,20 others could not confirm this finding. [21][22][23][24] However, the robustness of these studies was reduced by the way in which hematuria was evaluated (at the onset of the disease, at the time of renal biopsy, or by cross-sectional studies) without longitudinal data. 23,24 In other studies, urine dipsticks were used, and the magnitude of hematuria was not quantified.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] However, the robustness of these studies was reduced by the way in which hematuria was evaluated (at the onset of the disease, at the time of renal biopsy, or by cross-sectional studies) without longitudinal data. 23,24 In other studies, urine dipsticks were used, and the magnitude of hematuria was not quantified. 20 At the end of follow-up, 17.2% of our patients had reached ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Lin et al showed that microscopic hematuria was associated with increased risk of ESRD in 1,799 patients with stage 3 to 5 nondiabetic CKD. Whereas, there are several reports denying microscopic hematuria as a risk factor of CKD progression in patients with IgA nephropathy [5,6] …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that young persons with persistent isolated microscopic hematuria may indeed have an increased risk for ESRD as compared with individuals without this condition [4]. On the other hand, there are several contradictory results, ruling out the impact of microscopic hematuria on the outcome of IgA nephropathy [5,6]. Therefore, microscopic hematuria has not reached consensus as a risk factor of ESRD [7].…”
Section: Introductionmentioning
confidence: 99%